Religiositas dan Kinerja Pustakawan - Riya Fatmawati; Nurdin Laugu; Nurus Sa'adah (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional, 2023)
ABSTRACT Work is a form of endeavor in living life. Individuals who have a good level of faith believe that work is a mandate that must be carried out properly and with full responsibility. The librarian’s behavior at work reflects the maturity level of the religion he adheres to. The relationship between religiosity and performance can be from the activities of librarians at work. The purpose of this study was to determine whether individual religiosity influences the performance of a librarian university in West Sumatera. This study uses a qualitative method with a phenomenological approach. The measurement of religiosity uses five dimensions of religiosity: a dimension of religious belief, religious practice, religious feeling, religious impact, and religious knowledge. Data collection was carried out using field observation techniques, interviews, and documentation. The informants in this study are librarians’ universities in West Sumatera. The results from this study show there are three dimensions of religiosity that affect the performance of librarians including dimensions of religious belief, religious feeling, and religious effects. Meanwhile, the two dimensions of religiosity that do not have a positive effect on librarian performance are dimensions of religious practice and religious knowledge. Thus, it can be concluded that religiosity affects the performance of librarians. ABSTRAK Bekerja merupakan salah satu bentuk ikhtiar dalam menjalani kehidupan. Individu dengan tingkat religius yang baik meyakini sebuah pekerjaan adalah amanah yang harus dijalankan dengan baik dan penuh tanggung jawab. Perilaku pustakawan dalam bekerja mencerminkan tingkat kematangan agama yang dipahaminya. Hubungan religiositas dengan kinerja dapat dilihat dari aktivitas pustakawan dalam bekerja. Tujuan dari penelitian ini adalah mengetahui apakah religiositas individu berpengaruh terhadap kinerja pustakawan perguruan tinggi di Sumatera Barat. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi. Pengukuran religiositas menggunakan lima dimensi religiositas yaitu, dimensi religious belief, religious practice, religious feeling, religious effect, dan religious knowledge. Pengumpulan data dilakukan dengan teknik observasi lapangan, wawancara, dan dokumentasi. Informan dalam penelitian ini adalah pustakawan yang bekerja pada perpustakaan perguruan tinggi di Sumatera Barat. Hasil yang diperoleh dari penelitian ini adalah terdapat tiga dimensi religiositas yang mempengaruhi kinerja pustakawan, yaitu: dimensi religious belief, religious feeling, dan religious effect. Sementara itu, dua dimensi religiositas yang tidak berpengaruh positif terhadap kinerja pustakawan adalah dimensi religiousitas practice dan dimensi religious knowledge. Dengan demikian dapat disimpulkan bahwa religiositas mempengaruhi kinerja pustakawan.